Adult Anxiety Disorders in Relation to Trait Anxiety and Perceived Stress in Childhood. Issue 2 (October 2015) - Mundy, Elizabeth A.; Weber, Mareen; Rauch, Scott L.; Killgore, William D. S.; Simon, Naomi M.; Pollack, Mark H.; Rosso, Isabelle M.
It is well established that objective early life stressors increase risk for anxiety disorders and that environmental stressors interact with dispositional factors such as trait anxiety. There is less information on how subjective perception of stress during childhood relates to later clinical anxiety. This study tested whether childhood perceived stress and trait anxiety were independently and interactively associated with adult anxiety disorders. Forty-seven adults diagnosed with anxiety disorders ( M age = 34 yr., SD =11) and 29 healthy participants ( M = 33 yr., SD =13) completed the adult Perceived Stress Scale, the State-Trait Anxiety Inventory, and the Global Perceived Early Life Events Scale as a measure of perceived stress during childhood. In a logistic regression model, high childhood perceived stress (β = 0.64) and trait anxiety (β = 0.11) were associated with significantly greater odds of adult anxiety disorder. The association between childhood perceived stress and adult anxiety remained significant when controlling for adult perceived stress. These findings suggest that children's perception of stress in their daily lives may be an important target of intervention to prevent the progression of stress into clinically significant anxiety.